(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2026)
Rapid advancements in Information Technology (IT), mobile computing, the Internet, and Artificial Intelligence (AI) have revolutionized human life. While digital technologies have provided immense benefits in productivity, connectivity, and convenience, they have also contributed to shifts in social behaviors, human values, emotional expression, and interpersonal relationships. This paper examines how digital presence increasingly overshadows physical presence, the psychological and social consequences of this shift, and the ethical implications for society. Using multidisciplinary perspectives from psychology, sociology, and technology studies, the research argues that the overreliance on digital interactions reduces emotional richness, dilutes social responsibility, and challenges long-standing human values. The conclusion offers recommendations to balance digital engagement with physical human connection.